Critical Thinking Skills Profile And Changes Of Students' Ideas At Each Phase Of Think - Pair - Share Strategy In Learning Addictive And Psychotropic Substances - charyyeva, Mahri (2014)
This study investigated to contribute students' critical thinking skills and investigate students' ideas changes those refers to conceptual change with implementation a type of cooperative learning Think - Pair - Share strategy in learning addictive and psychotropic substances concept. The method used in this study is descriptive method that does not apply analytical data. The sample was taken based on convenient situation (n=9) at 8th grade in one of Bilingual Junior School Bandung. The qualitative data was gained through worksheet during teaching learning process that includes Think - Pair - Share strategy. Based on the study result, it is shown that students obtain both in-depth and surface level of critical thinking by finding available solutions on a problem, defend chosen solution, finding out weaknesses, and strengthen chosen solution. One of the concepts was reflection where students should reflect on their own thinking process, the result wasn't as suspected. At all, students are good in analyzing the available solutions regarding to a problem, students' critical thinking skills involves in making conclusions supported by logical reasoning. Whereas changes of students' ideas were present at each of Think - Pair - Share strategy phases, students ideas were not determinates as constant but changes regard to a concept. Key words: Think - Pair - Share, critical thinking skills, students' ideas change, addictive and psychotropic substances